Constitucionalismo global, control de convencionalidad y el derecho a huelga en Chile (2016)
n the Inter-American context, the control of conventionality promoted by the Inter-American Court of Human Rights is linked to the process of construction of an ius commune in human rights. Human rights are identified as norm of constitutional character. The universality of human rights allows its consideration as an aspect of global constitutionalism. This paper aims at determining whether the control of conventionality can be considered an expression of global constitutionalism within the Inter-American region. We hold that the control of conventionality in the Inter-American system has propelled the application of a minimum standard of human rights and has stimulated the emergence of an ius commune in human rights.